2019
DOI: 10.3390/jmse7040105
|View full text |Cite
|
Sign up to set email alerts
|

Fish Hybridization Leads to Uncertainty Regarding Ciguatera Fish Poisoning Risk; Confirmation of Hybridization and Ciguatoxin Accumulation with Implications for Stakeholders

Abstract: Globally, ciguatera fish poisoning (CFP) avoidance efforts rely primarily on local knowledge of the fish being consumed, its collection location, and association with illnesses. In 2016, several fish that appeared to be hybrids between a local commercially prized species, Ocyurus chrysurus, and a regionally prohibited species Lutjanus apodus (due to CFP concerns), were caught nearshore in United States Virgin Islands waters, leading to confusion regarding the safety of consuming the fish. The hybrid status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The accuracy of the data provided by this revisited CBA-N2a, relies, in part, on the availability of five viability controls, i.e., RCV, COV − , COV + , QCOV − and QCOV + that were established throughout the various stages of CBA-N2a in order to verify: (i) the initial (RCV control) and final viability of N2a cells (COV − controls), (ii) the efficiency of O/V treatment (COV + controls) and (iii) the detection of the specific mode of action of VGSC activators vs. inhibitors (QCOV − and QCOV + controls). If the use of percentages is recurrent in most studies to express cell viability results [7,8,32,33,36,37,43,46,53,59,62,63,[66][67][68]70,73,74,76,81,83,85,87,88,90,91,95,97,103,[106][107][108][109][110][111][112], the originality of our revisited CBA-N2a is to recommend the use of absorbance data by establishing a RCV control that characterizes the baseline viability of N2a cell layer prior to O/V treatment and toxin exposure. This RCV control serves as a reference from which all other viability controls as well as viability data of standard and samples depend.…”
Section: Performance Of the Revisited Cba-n2amentioning
confidence: 99%
“…The accuracy of the data provided by this revisited CBA-N2a, relies, in part, on the availability of five viability controls, i.e., RCV, COV − , COV + , QCOV − and QCOV + that were established throughout the various stages of CBA-N2a in order to verify: (i) the initial (RCV control) and final viability of N2a cells (COV − controls), (ii) the efficiency of O/V treatment (COV + controls) and (iii) the detection of the specific mode of action of VGSC activators vs. inhibitors (QCOV − and QCOV + controls). If the use of percentages is recurrent in most studies to express cell viability results [7,8,32,33,36,37,43,46,53,59,62,63,[66][67][68]70,73,74,76,81,83,85,87,88,90,91,95,97,103,[106][107][108][109][110][111][112], the originality of our revisited CBA-N2a is to recommend the use of absorbance data by establishing a RCV control that characterizes the baseline viability of N2a cell layer prior to O/V treatment and toxin exposure. This RCV control serves as a reference from which all other viability controls as well as viability data of standard and samples depend.…”
Section: Performance Of the Revisited Cba-n2amentioning
confidence: 99%
“…However, species implicated in CP can have wide geographical ranges, e.g., the Nassau grouper ( Epinephelus striatus ) transcend the jurisdictions of 43 nations or territories [ 142 ], or have a relatively small spatial home and hunting ranges, with occasional sporadic movements for spawning aggregations and migrations. Consumer avoidance of CP risk species can become complicated when identifiable characteristics used for phenotypically determining a species, like the head or skin, are removed during processing [ 143 , 144 ] or when species hybridize [ 145 ]. Therefore, the policies guiding CP harvest restrictions can be subverted by deliberate or inadvertent species substitution [ 146 ], or by falsifying capture location information [ 147 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, a meal remnant analysis remains the best scenario for confirmation of potential poisoning. In trace back instances from CP outbreaks, DNA-barcoding is a critical tool for the identification of the ciguatera-causing species [ 145 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 ]. Toxin identification, quantification, and DNA barcoding [ 194 ] can still be performed on the meal remnant even after cooking, yielding valuable information for cataloging CP events and causative fish species [ 114 , 186 , 195 ].…”
Section: Introductionmentioning
confidence: 99%
“…Novoveská and Robertson [2] by identifying spherical cells, most likely a morphological stage of the toxin-producing dinoflagellate Karenia brevis, as a source of brevetoxins in Mobile Bay, Gulf of Mexico, USA, suggesting that monitoring programs relying only on microscopy are not sufficient to properly evaluate the risk and that data on toxin occurrence is needed. Similarly, Loeffler et al [3] highlighted the importance of determining the toxin content, in this case regarding ciguatoxins, and not relying only on species identification, in this case fish species that are commonly recognized as toxin vectors. In their work, Loeffler and colleagues [3] revealed the presence of C-CTX-1 in a hybrid between a local commercially prized species Ocyurus chrysurus (male) and a regionally prohibited species Lutjanus apodus (female), collected from nearshore US Virgin Islands waters.…”
mentioning
confidence: 99%
“…Similarly, Loeffler et al [3] highlighted the importance of determining the toxin content, in this case regarding ciguatoxins, and not relying only on species identification, in this case fish species that are commonly recognized as toxin vectors. In their work, Loeffler and colleagues [3] revealed the presence of C-CTX-1 in a hybrid between a local commercially prized species Ocyurus chrysurus (male) and a regionally prohibited species Lutjanus apodus (female), collected from nearshore US Virgin Islands waters. Finally, Rodrigues et al [4] reported the first study investigating the presence of tetrodotoxin (TTX) and TTX analogues in bivalve mollusks from the Portuguese coast.…”
mentioning
confidence: 99%